Brazilian perspective on Material Transfer Agreements (MTA) and R&D between university-company (Research, Society and Development, 2023)
This article evaluates, based on a bibliographical and legislative review, the nature of the agreements that deals with the material transfer (MTA) destined for research and development (R&D) in the context of Academia-University/Enterprise relations, and under which assumptions they configure, or not, obligational considerations (ownership, as an example) pertaining to industrial property. The study indicates that, in general, the use of the Materials Transfer Agreement, or the stipulation of clauses of such nature in partnership agreements, is a necessary measure to avoid uncertainties that increase transaction costs. Research and Development activities are rarely carried out without requiring some resource from another entity (private or public), whose access raises questions related to past and future guarantees of industrial rights. The aim of the article is therefore to summarise the issues surrounding the transfer of materials used in scientific research, from the point of view of the university/company relationship.